Information Transfer : The Next Twenty-Five Years - Neelameghan, A.; Seetharama, S. (Journal of Information and Knowledge, 1976)
Presents scenarios and projections of the information environment and information transfer process in the next two decades, based on reports of Delphi and other studies. Ideas on information transfer-in education, medicine, business and management areas are presented as illustrative examples of the shape of things to come. Characteristics of the structure and power loci of the post-industrial information-conscious and information rich society, and the mutual influence of information and society are mentioned. The likely developments in information transfer technology, the role of the information worker of tomorrow, and the emerging economics of information are dealt with. Concludes proposing some issues, with special-reference to developing countries, for consideration.